Biodiversity and bioecology of Iraqi desert truffles (Pezizaceae) during season 2014 - Owaid, Mustafa Nadhim (Journal of Aridland Agriculture, 2016)
Desert truffles were a mystery to the ancient world of the Greeks and Romans but this did not prevent their culinary enjoyment and knowledge of several varieties from various locations. The hypogeous ascomycetes (desert truffles) were collected and identified from Hit market western Iraq with its prices and environment. Generally, two genera were observed viz., Terfezia sp. and Tirmania sp. Locally, Terfezia sp. called in Arabic â€œahraqâ€ or â€œjabaâ€ while Tirmania sp. called â€œzubaidiâ€ or â€œsheikhâ€ or â€œshiuokhâ€. These truffles live in mycorrhizal association with Helianthemum sp. or without any mycorrhizal association. Desert truffles appeared from last January to beginning of March 2014 in this Iraqi market. Its prices started from 65000 IQD/kg (around 52 USD/kg) then declined when high amounts of truffles are coming into market. Two factors, rainfall and exportation, effect on desert truffles prices. Some of amounts were exported to Baghdad or other places (in side), or Jordan (outside), thus that led to increase its prices, and the reverse is true.Â